Methods in Islamic Education - Besse Ruhaya; Juhri; Nurchamidah; Nurlaela; Muhammad Hamsah; Muhammad Muhaimin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Methods in Islamic education are crucial for effective learning, spiritual growth, and character development. Rooted in religious, biological, psychological, and sociological principles, these methods encompass classical approaches like Imla', qira'ah, lectures, discussions, and memorization, alongside contemporary methods like demonstrations, assignments, sociodrama, question-and-answer sessions, exemplary behavior, and habituation. Education outside school (Pendidikan Luar Sekolah) further complements Islamic education, providing lifelong learning opportunities. By employing this diverse range of methods, educators can effectively impart knowledge, instill Islamic values, and prepare individuals to contribute meaningfully to society.